SOAT1 Promotes Gastric Cancer Lymph Node Metastasis Through Lipid Synthesis - Zhu, Tingting; Wang, Zhangding; Zou, Tianhui; Xu, Lei; Zhang, Shu; Chen, Yali; Chen, Chen; Zhang, Weijie; Wang, Shouyu; Ding, Qingqing; Xu, Guifang (Frontiers in Pharmacology, 2021)
Emerging evidences demonstrate that metabolic reprogramming is a hallmark of malignancies, including gastric cancer (GC). Abnormal expression of metabolic rate-limiting enzymes, as the executive medium of energy metabolism, drives the occurrence and development of cancer. However, a comprehensive model of metabolic rate-limiting enzymes associated with the development and progression of GC remains unclear. In this research, we identified a rate-limiting enzyme, sterol O-acyltransferase 1 (SOAT1), was highly expressed in cancerous tissues, which was associated with advanced tumor stage and lymph node metastasis, leading to the poor prognosis of GC. It was shown that knockdown of SOAT1 or pharmacological inhibition of SOAT1 by avasimibe could suppress GC cell proliferation, lipid synthesis and lymphangiogenesis. However, overexpression of SOAT1 promoted these biological processes. Mechanistically, SOAT1 regulated the expression of cholesterol metabolism genes SREBP1 and SREBP2, which could induce lymphangiogenesis via increasing the expression of VEGF-C. In conclusion, our results indicated that SOAT1 promotes gastric cancer lymph node metastasis through lipid synthesis, which suggested that it may be a promising prognostic biomarker for guiding clinical management and treatment decisions.